Physical activity pre- and post-dementia: English Longitudinal Study of Ageing - Soni, Mira; Orrell, Martin; Bandelow, Stephan; Steptoe, Andrew; Rafnsson, Snorri; d'Orsi, Eleonora; Xavier, Andre; Hogervorst, Eef (Taylor & Francis, 2017)
Background: To inform public health interventions, further investigation is needed to identify: (1) frequency/intensity of everyday physical activity (PA) needed to reduce dementia risk; (2) whether post-diagnosis reduction in PA is associated with cognitive outcomes. Methods: Data from 11,391 men and women (aged ≥50) were obtained in the English Longitudinal Study of Ageing. Assessments were at baseline (2002-2003) and biannual follow-ups (2004-2013). Results: Older adults who carried out moderate to vigorous activity at least once per week had a 34%-50% lower risk for cognitive decline and dementia over an 8-10 year follow-up period. From pre- to post-diagnosis, those that decreased PA levels had a larger decrease in immediate recall score, compared to those that maintained or increased PA levels (adjusted for changes in physical function). Conclusion: These findings provide a guideline for everyday PA levels needed to reduce risk for dementia. Reduction in PA after diagnosis was also associated with accelerated cognitive decline.